Pengaruh Leverage, Profitabilitas, Likuiditas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Infrastruktur Di Bursa Efek Indonesia Tahun 2019-2023 - Jeremia, Eungeuline Eva; Arif, Amirul (Jurnal Pendidikan Akuntansi (JPAK), 2024)
The purpose of this study is to analyze the influence of leverage, profitability, liquidity, and company size on the value of infrastructure companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. This research is a quantitative study conducted using multiple linear regression analysis with secondary data obtained from the annual financial reports of infrastructure companies on the IDX. The sample of this study consists of 15 infrastructure companies selected using purposive sampling techniques. The sample criteria are that the companies must have complete financial reports and be active in stock trading on the IDX during the 2019-2023 period. The results of this study indicate that leverage has a significant negative effect on company value. Profitability, Liquidity, and company size do not have a significant effect on company value. Leverage, profitability, liquidity, and company size simultaneously have a significant effect on company value. This study provides implications for company management in decision-making to increase company value in the future through leverage, profitability, liquidity, and company size. This research also provides insights for investors in determining which companies are suitable for investment.